A comparative study of group delay equalizers for satellite communications. Issue 6 (21st February 2020) - Shafeghati, Mohsen; Ahmadi, Behzad; Torabi, Abdorreza
Abstract: This article presents a comparative study of four different group delay (GD) equalizers with a narrow band filter used as input multiplexer for a Ku‐band satellite transponder. A dual mode cylindrical filter with 36 MHz bandwidth is designed and fabricated. The filter GD is measured and two types of group‐delay equalizers are designed to fulfill the requirements of the transponder's GD mask. Two rectangular and two cylindrical equalizers are designed and their performance parameters, such as insertion loss and equalized bandwidth, are compared. In addition, a comparison between the designed first order (C‐section) and second order (D‐section) GD equalizers is done.